Computational Overview of Fluid Structure Interaction 2021
DOI: 10.5772/intechopen.95301
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Natural Convection and Entropy Generation of Water near Density Inversion in a Cavity Having Circular and Elliptical Body

Abstract: In this chapter, a water-filled square cavity with left hot wall and right cold wall was numerically investigated. The hot and cold wall temperatures are 10°C and 0°C respectively to examine the density inversion of natural convection water, i.e. water at 4°C. In the middle of the square, there are circular and elliptical bodies to study fluid–structure interaction in terms of the thermohydraulic behavior and entropy generation. 2D numerical simulation was performed using finite volume method in Ansys fluent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…where L(m) is distance between hot and cold wall. The local heat transfer coefficient is calculated by the formula [10,17]:…”
Section: Methodology 21 Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…where L(m) is distance between hot and cold wall. The local heat transfer coefficient is calculated by the formula [10,17]:…”
Section: Methodology 21 Mathematical Modelingmentioning
confidence: 99%
“…Some studies related to the entropy generation of water density inversion region can be found in previous literature. Phu and hap [10] investigated the entropy generation of a cavity with a circular and elliptical body inside. They reported the largest entropy generation for the cavity with the circular body and the smallest for the hollow cavity.…”
Section: Introductionmentioning
confidence: 99%